PENINGKATAN KUALITAS GARAM MELALUI PENGGUNAAN TEKNOLOGI GEOMEMBRAN DI IKM SANOLO JAYA DESA SANOLO KECAMATAN BOLO KABUPATEN BIMA - Ruslan Ruslan; Agrippina Wiraningtyas; Ahmad Sandi; Ariyansyah Ariyansyah (Politeknik Negeri Sriwijaya, 2020)
The problems faced by salt farmers in Sanolo Village, Bolo District include the low quality of salt so that it does not meet standards for use as industrial raw material. The activities of the PPPUD will be carried out by the development of the salt industry by applying technology to improve the quality of the people's salt in Sanolo Village, Bolo District, Bima Regency as consumption salt and industrial salt that meets SNI. In this activity, a plastic geomembrane was used as a crystallization table. The result is that the salt obtained in ponds using geomembrane plastic has a better quality than in ponds that use soil as a crystallization table. In addition, the amount of salt produced has increased by about 200%. As well as a change in the behavior of partner groups in the use of science and technology to produce salt.